2005
DOI: 10.1108/09513550510576125
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement in municipalities

Abstract: PurposeThis paper examines the actual and desired use of performance measures for management and external reporting purposes, as well as perceived impediments to their effective use.Design/methodology/approachA total of 334 senior administrators in Canadian municipalities participated in this survey study.FindingsSomewhat more efficiency measures than effectiveness measures have been used for various purposes. However, greater use was perceived desirable than actually occurred, particularly for effectiveness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 35 publications
0
19
0
10
Order By: Relevance
“…Based on these definitions, which are central to PMS design, a PMS is defined as 'a set of metrics used to quantify both efficiency and effectiveness of actions' (Neely, Gregory, & Platts, 1995, p. 81), while a KPI is 'a metric used to quantify the efficiency and/or effectivity of an action' (Neely et al, 1995, p. 80). To measure efficiency and effectiveness, four types of KPIs exist: input, process, output and outcome (Ammons, 1995;Hoque & Adams, 2011;Pollanen, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these definitions, which are central to PMS design, a PMS is defined as 'a set of metrics used to quantify both efficiency and effectiveness of actions' (Neely, Gregory, & Platts, 1995, p. 81), while a KPI is 'a metric used to quantify the efficiency and/or effectivity of an action' (Neely et al, 1995, p. 80). To measure efficiency and effectiveness, four types of KPIs exist: input, process, output and outcome (Ammons, 1995;Hoque & Adams, 2011;Pollanen, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here we follow Neely et al (1995), who defined performance measurement as 'the process of quantifying the efficiency and effectiveness of actions' (p. 1229). To facilitate performance improvements, it is therefore necessary that the criteria of efficiency and effectiveness in PMS design are met and, to this end, that the four types of KPIs -input, process, output and outcome measures -are considered (Ammons, 1995;Foltin, 1999;Hoque & Adams, 2011;Pollanen, 2005).…”
Section: Transparency and Design Criteria Of Pmssmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mandated public performance reporting is widespread in western countries (Moynihan 2008), Canadian local governments have largely been exempt. In his survey of senior managers in five Canadian provinces, Raili Pollanen (2005) found that only twenty per cent of his 334 respondents indicated that external reporting was required. Ontario and British Columbia are among the five provinces included in his survey, and both require local governments to report annually.…”
Section: From Performance Measurement To Performance Management In Lomentioning
confidence: 99%
“…Although there are a few studies of the ways in which elected officials use performance information (Askim 2007), there are no studies to date that have systematically compared the views of managers and elected officials in specific jurisdictions on the usefulness of performance measurement information for managing performance. Pollanen (2005) suggests that elected officials would probably not be interested in performance information. Indeed, for provincial, state, and national governments, a consensus is emerging that elected officials generally do not use performance information, or use it very sparingly (Bouckaert and Halligan 2008; Moynihan 2008).…”
Section: From Performance Measurement To Performance Management In Lomentioning
confidence: 99%